Abstract Number ‐ 210: Curative Embolization of Ruptured Pediatric Cerebral Arteriovenous Malformations - Giancarlo Saal‐Zapata; Aaron Rodriguez‐Calienes; Juan Vivanco‐Suarez; Milagros Galecio‐Castillo; Mudassir Farooqui; Cynthia Zevallos; Santiago Ortega‐Gutierrez (Stroke: Vascular and Interventional Neurology, 2023)
Introduction The incidence of ruptured cerebral arteriovenous malformations (AVMs) has increased as a consequence of the publication of the ARUBA trial. In the setting of ruptured AVMs, target embolization of high‐risk features can be considered to decrease the risk for recurrent hemorrhage. However, embolization with the intention to cure has not been well studied in ruptured AVMs. Furthermore, the role of primary curative embolization of pediatric AVMs is uncertain. Hence, we aimed to characterize the safety and efficacy of curative embolization for ruptured AVMs in pediatric patients. Methods Between 2010 and 2022, a retrospective analysis of all pediatric (≤18 years) patients who underwent curative embolization for ruptured AVMs was conducted in two institutions. Demographic data, clinical presentation, Spetzler‐Martin (SM) grade, associated high‐risk vascular structures, and procedural characteristics were retrieved. The safety (intraprocedural complications and mortality) and efficacy (complete angiographic obliteration after the last embolization session) were evaluated. Results Sixty‐eight patients (38 females; mean age 12.4 ± 3.4 years) underwent a total of 109 embolization sessions. The most frequent clinical presentation was headache (79%). There were 15 (22%) SM grade I lesions, 34 (51%) grade II, 14 (21%) grade III, and 4 (6%) grade IV. In 21 patients, twenty‐three high‐risk structures were observed (3 prenidal aneurysms, 12 intranidal aneurysms, 3 venous aneurysms, 2 varicose veins, 3 arteriovenous fistulae). Decompressive craniectomy with intracerebral hemorrhage evacuation was performed in 15 patients (22%). The mean number of sessions per patient was 1.6 (range 1 to 6) and n‐butyl cyanoacrylate was the most used embolic agent (30%). The transarterial approach was the most common (91%). The mean volume of embolic agents in each patient was 2.1 ml (range 0.1 to 6 ml). Seventeen intraprocedural complications (16% of procedures) were observed and no deaths were reported. In patients with high‐risk structures the rate of intraprocedural complications was 24%. The most common complication was microcatheter‐related vessel perforation (7%). Complete angiographic obliteration was achieved in 42 patients (62%). In 30 patients (44%) the AVM was occluded with a single embolization session. The rate of complete obliteration in patients with high‐risk structures was 62%. Conclusions Curative embolization of ruptured pediatric AVMs shows a high rate of intraprocedural complications, especially when high‐risk associated vascular structures are present. In addition, acceptable complete obliteration rates were found. Appropriate long‐term follow‐up in prospective studies tailored to the pediatric population are required to determine the best therapeutic approach.